Specific Temporal Distribution and Subcellular Localization of a Functional Vesicular Nucleotide Transporter (VNUT) in Cerebellar Granule Neurons - Menéndez-Méndez, Aida; Díaz-Hernández, Juan I.; Ortega, Felipe; Gualix, Javier; Gómez-Villafuertes, Rosa; Miras-Portugal, María T. (Frontiers in Pharmacology, 2017)
ATP is an important extracellular neurotransmitter that participates in several critical processes like cell differentiation, neuroprotection or axon guidance. Prior to its exocytosis, ATP must be stored in secretory vesicles, a process that is mediated by the Vesicular Nucleotide Transporter (VNUT). This transporter has been identified as the product of the SLC17A9 gene and it is prominently expressed in discrete brain areas, including the cerebellum. The main population of cerebellar neurons, the glutamatergic granule neurons, depends on purinergic signaling to trigger neuroprotective responses. However, while nucleotide receptors like P2X7 and P2Y13 are known to be involved in neuroprotection, the mechanisms that regulate ATP release in relation to such events are less clearly understood. In this work, we demonstrate that cerebellar granule cells express a functional VNUT that is involved in the regulation of ATP exocytosis. Numerous vesicles loaded with this nucleotide can be detected in these granule cells and are staining by the fluorescent ATP-marker, quinacrine. High potassium stimulation reduces quinacrine fluorescence in granule cells, indicating they release ATP via calcium dependent exocytosis. Specific subcellular markers were used to assess the localization of VNUT in granule cells, and the transporter was detected in both the axonal and somatodendritic compartments, most predominantly in the latter. However, co-localization with the specific lysosomal marker LAMP-1 indicated that VNUT can also be found in non-synaptic vesicles, such as lysosomes. Interestingly, the weak co-localization between VNUT and VGLUT1 suggests that the ATP and glutamate vesicle pools are segregated, as also observed in the cerebellar cortex. During post-natal cerebellar development, VNUT is found in granule cell precursors, co-localizing with markers of immature cells like doublecortin, suggesting that this transporter may be implicated in the initial stages of granule cell development.